Crossbreeding with Africander dam as basis. 3. Post-weaning growth performance of progeny of various sire-breeds - Mentz, A.H.; Els, D.L.; Coetzer, W.A. (1979)
Post-weaning growth performance was studied for 342 steers out of Africander cows and by Africander, Brahman. Charolais, Hereford and Simmental sires. In a system of intensive fattening, the latter three Bos taurus sire-breed progeny-groups performed strikingly better than the former two Bos indices sire-breed progeny-groups. Under ranching conditions, however, all crossbred groups outperformed the Africander controls. The progeny from both Bos indicus sire-breeds performed relatively better under ranching conditions than under intensive conditions. The simmentaler crossbreds also performed relatively better under the extensive conditions. Charolais and Hereford progenies, however, performed relatively better in the improved nutritional system.